Report of the Committee on India Vision 2020 - Planning Commission (Planning Commission Government of India, 2002)
The India Vision 2020 report presents a comprehensive roadmap for India’s socio-economic transformation over two decades, emphasizing employment generation, education, healthcare, and infrastructure development. With a target of creating 200 million jobs and achieving universal literacy, the report highlights the critical need for vocational training, technological adoption, and skill enhancement to harness the demographic dividend. It underscores sustainable agricultural practices, food security, and public health improvements while advocating decentralization, governance reforms, and e-governance for transparency and accountability. By integrating economic growth with human development, technological leadership, and global integration, Vision 2020 outlines a strategic pathway for inclusive, equitable, and sustainable national progress.
Planning Commission, Government of India, New Delhi 110001
Keywords: India Vision 2020; Employment Generation; Education Reform; Vocational Training; Food Security; Healthcare Development; Infrastructure Expansion; Human Development; Governance Reforms; Decentralization; Technological Advancement; Inclusive Growth